ONLINE LOAN PRACTICE (PIJOL) VIEWED FROM PERPSECTIVE OF THE BANKING LAW SYSTEM (STUDY IN MEDAN CITY) - Taufiq Wahyudi; Mustamam Mustamam; Mukidi Mukidi (Jurnal Ilmiah METADATA, 2021)
The phenomenon of online lending in society today has become quite an unsettling social phenomenon. Because online lending practices that charge high interest rates are not much different from loan sharks (loan sharks) who ensnare the poor. Many of the systems applied in online lending practices are not in accordance with the banking legal system. As for the problems in this study regarding how the legal provisions of online lending practices according to the banking legal system in Indonesia? How is the mechanism for implementing online loans currently developing in the community? What is the legal protection of borrowers in online loan practices? This type of research is normative juridical research, while the nature of the study is descriptive analysis. This research uses several approaches, namely the law and conceptual approach. The research data consisted of primary and secondary data sources. The data analysis used in this study is qualitative data analysis. Based on the results of the study, online loans in the perspective of banking law, can be said to be in accordance with the banking legal system. The online loan agreement is based on the legal agreement stipulated in the Civil Code as a general provision in the credit agreement which is also applied by banks. In addition, the online loan agreement also applies banking legal principles. The online loan implementation mechanism that is currently developing in the community is based on technology called Fintech Peer to Peer Lending, where there are three parties involved, namely: lenders, loan recipients and fintech providers. Legal protection for borrowers in the practice of online lending has yet to have legal certainty. The essence of the Financial Services Authority Regulation No. 77/POJK.01/2016, only directs that online loan service providers register with the OJK. This means that the substance of the OJK regulations has not fully provided protection for customers, both in terms of preventive and refressive efforts.